Sectoral Transformations in Neo-Patrimonial Rentier States: Tourism Development and State Policy in Egypt - Thomas Richter; Christian Steiner (German Institute of Global and Area Studies (GIGA), 2007)
This article challenges claims that liberalising state regulated markets in developing countries may induce lasting economic development. The analysis of the rise of tourism in Egypt during the last three decades suggests that the effects of liberalisation and structural adjustment are constrained by the neo-patrimonial character of the Egyptian political system. Since the decline of oil rent revenues during the 1980s tourism development was the optimal strategy to compensate for the resulting fiscal losses. Increasing tourism revenues have helped in coping with macroeconomic imbalances and in avoiding more costly adjustment of traditional economic sectors. Additionally, they provided the private elite with opportunities to generate large profits. Therefore, sectoral transformations due to economic liberalisation in neo-patrimonial Rentier states should be described as a process, which has led to the diversification of external rent revenues, rather than to a general downsizing of the Rentier character of the economy. – – Dieser Artikel stellt den Zusammenhang zwischen nachhaltiger wirtschaftlicher Entwicklung infolge der Liberalisierung staatlich regulierter Märkte in Entwicklungsländern in Frage. Die Analyse des Aufstiegs des Tourismussektors in Ägypten seit Anfang der 1970er Jahre zeigt, dass die Liberalisierung und Diversifizierung der ägyptischen Ökonomie maßgeblich durch den neopatrimonialen Charakter ihres politischen Systems bestimmt war. Infolge des Rückgangs der Erdölpreise seit den frühen 1980er Jahren wurde der Ausbau des Tourismussektors zur optimalen Entwicklungsstrategie, um Einnahmenverlust zu kompensieren. Die steigenden Tourismuseinnahmen halfen dem ägyptischen Staat, makroökonomische Ungleichgewichte auszugleichen und kostspielige Anpassungsprozesse in traditionellen Wirtschaftssektoren zu vermeiden. Darüber hinaus eröffnete die Tourismusentwicklung den privaten Wirtschaftseliten des Landes neue Möglichkeiten, erhebliche Profite zu realisieren. Sektorale Transformationen in neopatrimonialen Rentier-Staaten sollten deswegen vor allem als Rentendiversifizierung verstanden werden und weniger als Prozesse, die den Rentencharakter einer Volkswirtschaft im Allgemeinen verringern.
Keywords: H27; L83; O11; P26; 330; Egypt; rentier state; economic liberalisation; economic development; tourism; Entwicklungsstrategie; Strukturwandel; Tourismuswirtschaft; Rent Seeking; Politisches System; Governance-Ansatz; Ägypten